Effective tooth-bleaching protocols capable of reducing H2O2 diffusion through enamel and dentine - Soares, Diana G. [UNESP]; Basso, Fernanda G.; Pontes, Elaine C. V. [UNESP]; Garcia, Lucas da F. R. [UNESP]; Hebling, Josimeri [UNESP]; Souza Costa, Carlos A. de [UNESP] (Elsevier B.V., 2014)
Objectives: To evaluate the effects of experimental protocols on bleaching effectiveness and hydrogen peroxide (HP) diffusion through enamel and dentine.Methods: Enamel/dentine discs were subjected to six bleaching sessions, consisting of 1 or 3 applications of 17.5% or 35%-HP gel for 5/15 min, or 37% carbamide peroxide (CP) gel for 10/20 min. Discs undergoing the regular protocol (35%-HP; 3 x 15 min) constituted the positive control group. Colour change (Delta E) was assessed (CIE L*a*b* system) after each session. HP diffusion was quantified (sessions 1, 3, and 6) in enamel/dentine discs adapted to artificial pulp chambers. Data were analysed by Pillai's Trace and Bonferroni test, or by one-way ANOVA and SNK/Tamhane's test (alpha = 5%).Results: All tooth-bleaching protocols significantly increased the Delta E values. A reduction in HP diffusion and no significant difference in Delta E compared with the positive control were observed for the following bleaching protocols: 17.5%-HP 3 x 15 min, at the 4th session; and 35%-HP 1 x 15 and 3 x 5 min, at the 5th session. HP diffusion in the 37%-CP 3 x 20 min bleaching protocol was statistically similar to that in the positive control. The other experimental bleaching protocols significantly decreased HP diffusion through enamel/dentine discs, but the Delta E values were statistically lower than those observed in the positive control, in all sessions.Conclusion: Shortening the contact time of a 35%-HP gel or reducing its concentration produces gradual tooth colour change and reduced HP diffusion through enamel and dentine.Clinical significance: A reduction in HP concentration, from 35% to 17.5%, in a bleaching gel or shortening its application time on enamel provides a significant tooth-bleaching improvement associated with decreased HP diffusion across hard dental tissues. Therefore, these protocols may be an interesting alternative to be tested in the clinical situation. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Tooth bleaching; Hydrogen peroxide; Enamel; Dentine